Examining The Effects Of Cell Phone Use On The Mental Well-Being And Academic Performance Of Pre-Health And Nursing Students - WANG Jing; CHANDRA MOHAN VASUDEVA PANICKER; Aminul Islam (Revista Electronica de Veterinaria, 2024)
Researchers are now in the mobile phone age. Without knowing the risks, which might include cancer and other health problems, it is not "quite" safe to use these medications. While information on cancers caused by mobile phone radiation is accessible, there must be more investigation into the negative psychological and physiological effects, especially on heavy users like college students. This research set out to answer the question, "How does mobile phone use affect the mental health of college students enrolled in professional courses at urban institutions?" by looking at this very question. Steps and elements: Students from both urban and rural locations, ranging in age from 17 to 23, were selected at random and given a pre-test questionnaire about the impact of excessive mobile phone usage on psychological health. Result: Of those who reported symptoms, 51.47 percent had headaches, and 50.79 percent experienced annoyance or anger. Other common mental symptoms include difficulty concentrating and doing well in school, insomnia, anxiety, and related disorders. The heaviest mobile phone users tend to be young people, therefore it’s important to educate them about the potential mental health risks of excessive cell phone use and encourage them to take necessary precautions. The reason for this is because the population with the highest mobile phone usage is the younger generation. Some of the possible solutions put up include decreasing reliance on technology, decreasing the amount of time spent conversing, and increasing the focus on messaging.